2015
DOI: 10.5296/ijafr.v5i1.7394
|View full text |Cite
|
Sign up to set email alerts
|

Association between Corporate Social Responsibility Disclosures and Firm Value – Empirical Evidence from Vietnam

Abstract: A number of studies in Corporate Social Responsibility (CSR) have suggested that corporates accountable for social responsibilities had better financial performance. However, this (HOSE) and Hanoi (HNX) were investigated from 2010 to 2013. Content of annual reports were analyzed to measure corporate social responsibilities, and Tobin's Q ratio was proxied for firm value. Regression analysis tests indicated that social responsibility disclosures are associated with following year's firm value. Specifically, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
32
1
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(42 citation statements)
references
References 15 publications
5
32
1
4
Order By: Relevance
“…The explanatory power of the model (R 2 ) is about 27.6%, while the adjusted R 2 is about 24.7%. The coefficient related to firm profitability (ROA) is positive (0.005) but not significant at conventional levels (t = 0.03 and p = 0.978), confirming the mixed results on the relationship between CSR disclosures and firm value (Hirigoyen & Rehm, 2015;Nguyen et al, 2015). This result does not support our first hypothesis.…”
Section: Results Of the Multiple Regression Modelscontrasting
confidence: 58%
See 1 more Smart Citation
“…The explanatory power of the model (R 2 ) is about 27.6%, while the adjusted R 2 is about 24.7%. The coefficient related to firm profitability (ROA) is positive (0.005) but not significant at conventional levels (t = 0.03 and p = 0.978), confirming the mixed results on the relationship between CSR disclosures and firm value (Hirigoyen & Rehm, 2015;Nguyen et al, 2015). This result does not support our first hypothesis.…”
Section: Results Of the Multiple Regression Modelscontrasting
confidence: 58%
“…Haryono and Iskandar (2015) classified empirical studies on the CSR-CFP relationship into three main categories: studies showing a positive relationship between the CSR and firm value (Aggarwal, 2013;Bidhari, Salim, & Aisjah, 2013); studies reporting no relationship between CSR and firm value because of the lack of understanding of their complex relationship (Tjia & Setiawati, 2012;Nyirenda, Ngwakwe, & Ambe, 2013). Finally, other studies showed a mixed or negative relationship between CSR disclosures and firm value (Hirigoyen & Rehm, 2015; Nguyen, Tran, Le, Nguyen, & Trinh, 2015). Dhaliwal, Li, Tsang, and Yang (2011) examined a potential benefit associated with the initiation of voluntary disclosure of CSR activities: a reduction in firms' cost of equity capital.…”
Section: Hypothesis Related To the Impact Of Csr On Firm Valuementioning
confidence: 99%
“…These findings supported Suhartati et al (2011) and Widyanti (2014), who proved that the area of CSR disclosure did not affect the firm value. These findings rejected Sarvaes & Tamayo (2012), Adeneye (2015) and Nguyen (2015), who proved the positive impact of CSR on firm value.…”
Section: Discussionmentioning
confidence: 75%
“…Sarvaes & Tamayo (2012) prove that CSR's activity and disclosure can add value to the company because CSR provides a good image so that loyal customers buy products produced by the company. Adeneye (2015) and Nguyen (2015) prove that CSR's disclosure and activity influence positively on firm value.…”
Section: Effect Of Corporate Social Responsibility On Price To Book Vmentioning
confidence: 99%
See 1 more Smart Citation